PENGARUH STRUKTUR MODAL, LEVERAGE, PROFITABILITAS, LIKUIDITAS DAN TAXPLANNING TERHADAP NILAI PERUSAHAAN: (Studi Kasus Terhadap Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Ratna Ayu Murti; Indra Lila Kusuma; Maya Widyana Dewi (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
Thisi research aimsi toi determinei thei influence ofi capitali structure, leverage, profitability,iliquidity, and tax planning on the value of consumer goods sector manufacturing companies listed on the Indonesian Stock Exchange in 2020-2022. Thisi research typei is quantitative research. The data collection technique used is documentation technique with secondary data. The population studied in this research is all manufacturing companies in the consumer goods sector. Sampling in this research used a purposive sampling technique and a sample of 51 was obtained. This testing method in this research used descriptive statistical tests, classical assumption tests, F tests, and determination test. The results of the F test get a significance value of 0,000 < 0,05 so that the model is suitable for research. The results of the t test from this research are that capital structure and profitabilty influence company value of 0,000 < 0,05. On the other hand, leverage has a significant negative effect on company value, as evidenced by the calculated t value of -3,325 < t Table 2,0141 and a significance value of 0,002 < 0,05 Then liquidity and tax planning have no effect on company value because their respective significance values ​​are 0.096 > 0.05 and tax planning has a significance value of 0.202 < 0.05. Form the results of the coefficient of determination test, we get a result 0,522 which means that the variables capital structure, leverage, profitability, liqudity and tax planning in explaining company value are 52,2% and the remaining 47,8% is explained by other variables.